HUBUNGAN DUKUNGAN KELUARGA TERHADAP TINGKAT STRES LANSIA YANG DITINGGAL PASANGANNYA - Imelda " Armie; Darwin " Karim; Yulia Irvani Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract This research aimed to determine the relationship between family support and level of elderly single stress who left her partner. This study research used descriptive correlation method with cross sectional approach. The number of sample were 91 elderly with purposive technique sampling who met criteria of inclusion in Puskesmas Bukit Kapur and Posyandu lansia Dumai city. The data was collected by using family support questionnaire and level of stress questionnaire CES-D (Center for Epidemilogic Studies Depression Scales). Both questionnaires were modified and tested for validity and reability. Data was analyzed using chi square test.The study showed that was a relationship between family support and level of elderly single stress who left her partner (p value 0.000 < alpha 0.05). The research suggest that family  must give support to elderly single who left her partner to decrease level of stress.  Keywords: Family support, level of stress, elderly single who left her partner